Leitura, princípios do sistema alfabético do português brasileiro e ensino de leitura/escrita - Flôres, Onici Claro (Linguarum Arena, 2017)
The present article is based on Aaron and Joshi (1989), GirolamiBoulinier, Pinto (1994), Pinto (1998) and Grabe (2009), researchers which had confirmed through their studies the need to link research on reading concerning the writing systems of the learners. The article also highlights the research of Scliar-Cabral (2003), a work in which the author makes a detailed study on the principles of the Brazilian Portuguese alphabetic system. In the aforementioned investigations, which mostly involved only the written alphabetic systems, the researchers based their studies on the analysis of phonological fundamentals of writing when the learner was starting to read, although the tradition of cognitive psychology is to investigate reading in a dissociated and independent mode. Therefore, the objective of this study is to propose the approach of reading difficulties, or lack of reading or even problems of reading learning in the school context, considering two analytical focuses: the nature of the orthographic system and the prevention and early detection of pathological cases (developmental dyslexia). For this purpose, two main sources of reading studies: biological (natural sciences) and the human and social sciences (Fijalkow 2014). The proposal aims to collect information from different sources in order to enable the construction of an analytical foundation to support the elementary education teachers more effectively as it regards to the relations between reading, phonology and orthography in Brazilian Portuguese. According to this perspective, three reading routes are presented as an alternative for theoretical and methodological basis instead of dual route, which is usually referred in studies regarding the school context. Finally, the presented proposal is justified due to the nature of language (psychological and social); at last, it is reiterated that the focus set of reading/writing system requires a description/explanation placing the beginner in reading, as the situational, social and cultural context. This can be done considering its variety of speech (incidental acquisition) and reading learning, concerning the orthographic system in which the reader is learning how to read/write.